The Effect of Concrete Quality on the Nominal Moment of Concrete Beams After 28 Days at the Operational Control Station of PT. Pertamina Gas - Bilson Bilson; Petrus Haryanto Wibowo (Fakultas Teknik Sipil dan Perencanaan, 2023)
Reinforced concrete is a concrete structure that has reinforcement in the form of reinforced steel. The strength of reinforced concrete relies on several factors, one of which is the quality of the concrete. However, the actual onsite concrete quality condition is always different from the planned concrete quality, so it is necessary to test the quality of the concrete. In this study, an analysis of the effect of concrete quality on the nominal beam moment will be carried out at the Operational Control Station (SPO) owned by PT. Pertamina gas. The method that will be used in this research is a comparative quantitative method where the results of the research are in the form of comparison of the nominal moment value of a beam at SPO on the onsite concrete quality compared to planned concrete quality. The quality planned concrete used was the K-300 quality on day 28 as well as the onsite concrete quality obtained in the PMRK-EPC-00-QAC-NOI-708 document. From the results of this study, the design concrete quality (fc' = 24.9 MPa) produces a nominal moment of 166,432 kNm with a value of a = 88,651 mm and the onsite concrete quality (fc' = 35,722 MPa) produces a nominal moment of 174 kNm with a value of a = 61,794 mm. From the results of the study, it was found that the quality of the concrete had a very little effect on the nominal beam moment. an increase in the quality of concrete by 30.29% only resulted in an increase in the nominal moment of 4.349% from the nominal moment of planned concrete quality.